Implementation of health education on perineal wound care for postpartum mother’s knowledge - Feni Elda Fitri; Eva Yunitasari; Rahayu Safitri (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: A mother who has just given birth often experiences perineal tears due to episiotomy or spontaneous tears. Perineal wounds are tears that occur during childbirth, whether spontaneous or due to episiotomy. If proper care is not taken, it can lead to dangerous complications, such as infections in the bladder or birth canal. Purpose: to determine the implementation of health education on perineal wound care regarding the knowledge of postpartum mothers. Method: The knowledge level of both respondents before being given education was respondent 1 Ny.M (45%) and respondent 2 Ny.K (55%) which falls into the category of low knowledge level. After receiving education, the knowledge level of respondent 1 Ny.M (85%) and respondent 2 Ny.K (95%) results were categorized as good knowledge. Results: Education on perineal wound care show that there is an increase in mothers' knowledge levels after being provided with education. Conclusion: This education can enhance postpartum mothers' understanding of perineal wound care and can be beneficial for the development of maternity nursing knowledge.